IMPLEMENTASI METODE ROLE PLAYING DALAM PENINGKATAN MOTIVASI BELAJAR SISWA - Naelasari, Desy (ILJ: Islamic Learning Journal, 2024)
Abstract:In the subject of Islamic Religious Education students find it difficult to understand the subject matter, learning tends to be centered on the teacher while students are passive, the teacher uses the lecture method so that motivation in student learning is lacking. One of them is the teacher using the Role Playing method, Role playing is a game in a story with a clear purpose or story while in the world of education, Role playing is a planned learning activity designed to achieve specific educational goals. This thesis discusses the Implementation of the Role Playing Method in Increasing Student Learning Motivation in Islamic Religious Education (PAI) Subjects at SMPN 1 Mojowarno . This study aims (1) to describe how students' learning motivation in PAI subjects at SMPN 1 Mojowarno, (2) to describe the application of the role playing method to increase student motivation in PAI subjects at SMPN 1 Mojowarno. This research is a qualitative research using a qualitative descriptive design, data collection techniques used are interviews, observation, non-participant, and documentation. Data is analyzed by means of data reduction (data reduction), display data collection (data presentation), and conclusion ( verification) (conclusion). The technique of testing the validity of this research data is by extending observations, increasing persistence, triangulation and using reference materials. The conclusions of this study are (1) Student motivation in the subject of Islamic Religious Education (PAI) at SMPN 1 Mojowarno Jombang includes: Diligently facing assignments, Tenacious in facing difficulties , Showing interest in various problems, Prefers to work independently, Not quickly bored with assignments, and Can defend his opinion. (2) The implementation of the role playing method in increasing student learning motivation in the Islamic Religious Education subject at SMPN 1 Mojowarno Jombang consists of: Planning a role playing learning program in the form of lesson plans (RPP), student handbooks (LKS), textbooks, or from other sources. The implementation of role playing learning methods includes: Making problems, Appointing participants, Playing roles, Observing and taking notes, Comments from students, and Evaluation of learning in the role playing method in the form of assessment rubrics, by checking whether it is appropriate or not with what has been assigned.